Factors influencing physiotherapy decisions between restorative and compensatory gait rehabilitation: an Italian multicenter study - Mestanza Mattos, Fabiola G.; Bowman, Thomas; Marazzini, Francesca; Salvalaggio, Silvia; Allera Longo, Cristina; Bocini, Serena; Bonci, Viviana; Materazzi, Francesco G.; Pelosin, Elisa; Putzolu, Martina; Turolla, Andrea; Mezzarobba, Susanna; et al. (Frontiers in Neurology, 2024)
Background and Purpose This study aimed at investigating the factors that influence physiotherapists' decision in choosing a restorative or compensatory rehabilitation during gait training in people with neurological disorders (PwND) and the different treatments used in the approaches. Methods This cross-sectional analysis used the baseline data from an observational cohort study. We analysed data from 83 PwND (65 people after stroke, 5 with multiple sclerosis, and 13 with Parkinson's disease) who underwent at least 10 sessions of physiotherapy (PT) focusing on gait function. Performance was quantified using the Modified Dynamic Gait Index (MDGI), three impairment domains of Fugl-Meyer Assessment for lower extremity (mFM-LL), Activities-specific Balance Confidence (ABC), modified Barthel Index (mBI), Mini-Mental State Examination (MMSE), and Motivational Index (MI). Forty-three physiotherapists completed a treatment report form categorizing the rehabilitation approach and specifying treatments used (e.g. resistance training, proprioceptive exercises, etc). Results Fifty-six subjects underwent restorative rehabilitation approach. The univariate predictors of restorative approach were being in the subacute phase with a disease onset of less than 180 days, (Odds Ratio[95%CI]; 3.27[1.19-9.24]), mFM-LL (1.25[1.11-1.44), MMSE (0.85[0.67-1.00]), and number of sessions (1.03[1-1.01]). Backward stepwise analysis found an association between restorative and subacute phase (36.32[4.11-545.50]), mFM-LL (3.11[1.55-9.73]), mBI (1.79[1.08-3.77]), MMSE (0.46[0.25-0.71]) and the interaction between mFM-LL and mBI (0.99[0.98-1.00]). No statistically significant association between treatments used and approach was found (p=.46). Discussion and Conclusions The restorative approach was more commonly used to improve gait. The main variables associated with this approach were: being in the subacute phase of the disease, a low level of impairment, and a high level of functional independence at baseline. However, few differences were found between treatments used for the restorative or compensatory approaches, as similar PT treatments were used for both.